Estimating the costs of surgical innovations: the case for subthalamic nucleus stimulation in the treatment of advanced Parkinson's disease. - McIntosh, E; Gray, A; Aziz, T (2003)
We estimated the current cost of deep brain stimulation surgery targeted on the subthalamic nucleus. The method used was a cost analysis using typical resource use patterns and unit costs from a leading surgical centre, detailed equipment costs from the manufacturer, and sensitivity analysis. Resource use was based on patients with advanced Parkinson's disease. The main outcome measure was the likely total health service costs per patient, including preoperative assessment, surgery, and postoperative management over a 5-year period. The preoperative assessment, surgery, and discounted follow-up costs associated with subthalamic nucleus surgery were estimated at approximately UK Pounds 32,526 per patient over 5 years. Almost 70% of these costs are attributable to the initial costs of the equipment and the likely follow-up and replacement costs of the equipment. These costs will be affected mainly by future equipment costs and their replacement period and are relatively insensitive to preoperative assessment staff costs, length of hospital stay after surgery, and imaging costs. This cost estimate should be of use to researchers, health care managers, policy makers, and surgeons working in this area. Providing an estimate of the cost of this new procedure will provide a baseline for tracking future changes in costs and will assist the production of cost-effectiveness estimates.